Both Two CtACO3 Transcripts Promoting the Accumulation of the Flavonoid Profiles in Overexpressed Transgenic Safflower - He, Beixuan; Zhang, Yanjie; Wang, Lunuan; Guo, Dandan; Jia, Xinlei; Wu, Jianhui; Qi, Shuyi; Wu, Hong; Gao, Yue; Guo, Meili (Frontiers in Plant Science, 2022)
The unique flavonoids, quinochalcones, such as hydroxysafflor yellow A (HSYA) and carthamin, in the floret of safflower showed an excellent pharmacological effect in treating cardiocerebral vascular disease, yet the regulating mechanisms governing the flavonoid biosynthesis are largely unknown. In this study, CtACO3, the key enzyme genes required for the ethylene signaling pathway, were found positively related to the flavonoid biosynthesis at different floret development periods in safflower and has two CtACO3 transcripts, CtACO3-1 and CtACO3-2, and the latter was a splice variant of CtACO3 that lacked 5’ coding sequences. The functions and underlying probable mechanisms of the two transcripts have been explored. The quantitative PCR data showed that CtACO3-1 and CtACO3-2 were predominantly expressed in the floret and increased with floret development. Subcellular localization results indicated that CtACO3-1 was localized in the cytoplasm, whereas CtACO3-2 was localized in the cytoplasm and nucleus. Furthermore, the overexpression of CtACO3-1 or CtACO3-2 in transgenic safflower lines significantly increased the accumulation of quinochalcones and flavonols. The expression of the flavonoid pathway genes showed an upward trend, with CtCHS1, CtF3H1, CtFLS1, and CtDFR1 was considerably induced in the overexpression of CtACO3-1 or CtACO3-2 lines. An interesting phenomenon for CtACO3-2 protein suppressing the transcription of CtACO3-1 might be related to the nucleus location of CtACO3-2. Yeast two-hybrid (Y2H), glutathione S-transferase (GST) pull-down, and BiFC experiments revealed that CtACO3-2 interacted with CtCSN5a. In addition, the interactions between CtCSN5a and CtCOI1, CtCOI1 and CtJAZ1, CtJAZ1 and CtbHLH3 were observed by Y2H and GST pull-down methods, respectively. The above results suggested that the CtACO3-2 promoting flavonoid accumulation might be attributed to the transcriptional activation of flavonoid biosynthesis genes by CtbHLH3, whereas the CtbHLH3 might be regulated through CtCSN5-CtCOI1-CtJAZ1 signal molecules. Our study provided a novel insight of CtACO3 affected the flavonoid biosynthesis in safflower.